IMMOBILIZATION OF PHENYLALANINE AMMONIA-LYASE ON HYDROXYAPATITE AND HYDROXYAPATITE COMPOSITES - BARTHA-VARI, Judith-Hajnal; ELEKES-DARABONT, Renáta; BARABÁS, Laura-Edit; BARABÁS, Réka (Studia Universitatis Babeș-Bolyai Chemia, 2021)
A new and efficient immobilization method of phenylalanine ammonia-lyase was obtained using hydroxyapatite (HAP) and hydroxyapatite - carbon nanotube, gelatin and chitosan - composites (HAP-CNT, HAP-GEL and HAP-CS) as support material. HAP and HAP composites were characterized by transmission electron microscopy (TEM), laser diffraction particle size analyzer and XRD measurements. The obtained nanobioconjugates were tested in the ammonia elimination reactions from L-phenylalanine (L-1). The reusability and the time-course profile of the immobilized enzyme preparation was also tested. While the biocatalyst obtained by using HAP-CS-15 as support material provided the highest conversion rate in the ammonia elimination reaction from L-1 (98,1% compared to 98,5% obtained using the non-immobilized enzyme), the most stable biocatalyst proved to be HAP-PAL, which maintained more than 80% of its initial activity even after 5 cycles of reuse.